2020
DOI: 10.1108/jes-09-2019-0444
|View full text |Cite
|
Sign up to set email alerts
|

Company performance and optimal capital structure: evidence of transition economy (Russia)

Abstract: PurposeThe paper analyzes the effects of the capital structure on company performance (return on assets). The analysis is conducted in a large sample of high-tech manufacturing and service companies in the transition economy (Russian Federation). In addition to the aggregated analysis, separate investigations are conducted to scrutinize the impact of company age, size and location factors (the effects of agglomerations). This research postulates the existence and variability of the optimal capital structure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 62 publications
2
13
0
Order By: Relevance
“…It was found that Total Debt to Total Assets (TDTA) correlate positively to profitability measured by ROE. Nawaz et al (2011) and Spitsin et al (2020) found that the TDTA ratio has a significant and positive influence on Tobin's Q, ROE, and ROA. The results confirm that high percentage of debt in CS favorably impact on firm's performance.…”
Section: Theoretical Background and Previous Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…It was found that Total Debt to Total Assets (TDTA) correlate positively to profitability measured by ROE. Nawaz et al (2011) and Spitsin et al (2020) found that the TDTA ratio has a significant and positive influence on Tobin's Q, ROE, and ROA. The results confirm that high percentage of debt in CS favorably impact on firm's performance.…”
Section: Theoretical Background and Previous Literaturementioning
confidence: 99%
“…So, the key main concern of our study is to examine the relationship between CS and FP in the Jordanian environment. Numerous researches have examined the relationship between CS and FP in developed countries like (Berger & Patti, 2006;Margaritis & Psillaki, 2007;Li et al, 2019;Spitsin et al, 2020), nevertheless, this study is directed to an emerging market, i.e., the Jordanian market whereby a few studies investigated the relationship between CS and FP (e.g. Shamsuddin et al, 2018;Tayem, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The findings show substantial negative influence of CS on FP which supports pecking order theory. Spitsin et al (2020) analyzed the influence of CS on performance of high-tech firms of Russia. The data was gathered from 1826 firms during 2013-2017.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Tannous, 2016; Mashayekhi & Mashayekh, 2008;Spitsin, Vukovic, Anokhin, & Spitsina, 2020;M.-C. Vu, Phan, & Le, 2018).…”
mentioning
confidence: 99%
“…Empirical tests of the relationship between capital structure and business performance show positive and negative contradictory conclusions, also implying a nonlinear relationship between the two. Scholars also used the quadratic function and quantile regression model to attempt to calculate the optimal capital structure (A. N. Berger & Bonaccorsi di Patti, 2006;Margaritis & Psillaki, 2010;Schorr & Lips, 2019;Spitsin et al, 2020). Ownership structure is the foundation of corporate governance (Arosa et al, 2010), determines the choice of capital structure (Brailsford, Oliver, & Pua, 2002;Chakraborty, 2018;Jiraporn & Liu, 2008;Le & Tannous, 2016;Lee & Kuo, 2014;Margaritis & Psillaki, 2010), and ultimately affects changes in corporate value.…”
mentioning
confidence: 99%